A new deep-sea palaemonid shrimp assigned to Periclimenes Costa, 1844 (Decapoda: Caridea) from the West Mariana Ridge, northwestern Pacific - Komai, Tomoyuki; Tsuchida, Shinji; Fujiwara, Yoshihiro (Zootaxa, 2023)
A new palaemonid species, Periclimenes variabilis, is described and illustrated on the basis of four specimens from the Ritto Seamount, West Marina Ridge, northwestern Pacific, at depths of 642–666 m. Specimens of the new species were collected with an unidentified hexacoral of Primnoidae (Cnidaria), an antipatharian octocoral Leiopathes sp. (Cnidaria), and an unidentified crinoid (Echinodermata), suggesting association with those invertebrates. Morphological comparison and molecular phylogenetic analyses using the mitochondrial 16S ribosomal RNA and cytochrome C oxidase subunit I genes indicate that the new species is closest to Periclimenes uniunguiculatus Bruce, 1990 although the possession of more than two spiniform setae on either side of the telson in the new species is consistent with the generic diagnosis of Bathymenes Kou, Li & Bruce, 2016. In reference to the close relationship to the species currently assigned to Periclimenes Costa, 1844 and the unsettled taxonomy of the genus, the new species is provisionally assigned to Periclimenes. Differentiating characters between the new species and closely related taxa are discussed.